(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
Artificial intelligence has revolutionized the financial industry, ushering in an era of unprecedented advances in decision-making, risk management, and customer service. As artificial intelligence technologies continue to develop, their impact on financial practices will only grow. This article discusses the potential applications of AI in finance, including banking. The author concludes that AI is applied in the financial sector at three levels: public finance (budget planning, debt management, and tax administration); corporate finance (risk management, financial planning, and investments); and household finance (personal financial management, credit scoring, and investment advice).